Mapping Soft Drink Consumption in West Bengal - A Case Study of the Beverages Industry - Naskar, Subhankar; Pandit, Suman; Jayprakash, Ajay Chauhan (International Journal of Computer Sciences and Engineering, 2025)
In recent years, the beverage industry has become a large and rapidly growing sector in India. Day by day, soft drinks have become a foremost in the daily lives of many urban consumers, particularly among the youth and working population. This study explores the patterns, preferences, and influencing factors behind soft drink consumption in West Bengal, a state where tradition and culture meet modern lifestyle choices. Through surveys conducted across various age groups and socio-economic backgrounds, this research uncovers not only the frequency and types of beverages consumed but also the cultural, climatic, and marketing-driven reasons behind these choices. This study further investigates the consumption patterns of soft drinks across the state, focusing on who drinks them, how they are influenced, and where they prefer to buy them.